Age differences in outcome after mild traumatic brain injury: results from the HeadSMART study. (2nd January 2020) - Richey, Lisa N.; Rao, Vani; Roy, Durga; Narapareddy, Bharat R.; Wigh, Shreya; Bechtold, Kathleen T.; Sair, Haris I.; Van Meter, Timothy E.; Falk, Hayley; Leoutsakos, Jeannie-Marie; Yan, Haijuan; Lyketsos, Constantine G.; et al.
Abstract: This study longitudinally examined age differences across multiple outcome domains in individuals diagnosed with acute mild traumatic brain injury (mTBI). A sample of 447 adults meeting VA/DoD criteria for mTBI was dichotomized by age into older (≥65 years; n = 88) and younger (<65 years; n = 359) sub-groups. All participants presented to the emergency department within 24 hours of sustaining a head injury, and outcomes were assessed at 1-, 3-, and 6-month intervals. Depressive symptoms were assessed using the Patient Health Questionnaire–9 (PHQ-9), post-concussive symptoms (PCS) were ascertained with the Rivermead Post-Concussion Questionnaire (RPQ), and functional recovery from the Extended Glasgow Outcome Scale (GOSE). Mixed effects logistic regression models showed that the rate of change over time in odds of functional improvement and symptom alleviation did not significantly differ between age groups ( p = 0.200–0.088). Contrary to expectation, older adults showed equivalent outcome trajectories to younger persons across time. This is a compelling finding when viewed in light of the majority opinion that older adults are at risk for significantly worse outcomes. Future work is needed to identify the protective factors inherent to sub-groups of older individuals such as this.